Concrete sulfate corrosion coupled with hydraulic pressure. Issue 1 (2nd January 2020) - Du, Jianmin; Li, Guo; Wu, Junhui
Abstract: A type of sealed steel box was designed to simulate sulfate attack and hydraulic pressure on concrete. Cup-shaped concrete specimens with water/cement (w/c) ratios of 0.4, 0.5, and 0.6 were fabricated. During the 270 days corrosion time, corrosion behavior on concrete surfaces was observed every 30 days. The extent of damage on concrete was calculated on the basis of the results of periodic ultrasonic testing. After the completion of experiments, X-ray fluorescence analysis was conducted on the element contents at different depth locations of partial specimens. Experimental results showed that hydraulic pressure accelerated the sulfate attack on concrete, and high pressure yielded serious damage. In comparison with zero pressure, the accelerating coefficients of 0.1, 0.2, and 0.3 MPa hydraulic pressures were 1.48, 1.75, and 2.35, respectively. Hydraulic sulfate corrosion can bring additional sulfate ions into concrete and cause chemical and physical sulfate corrosions on concrete simultaneously, thereby resulting in serious damage on concrete. The reduction of w/c ratio and incorporation of fly ash are beneficial for concrete to resist hydraulic sulfate attack.